2018
DOI: 10.1186/s12967-018-1483-x
|View full text |Cite
|
Sign up to set email alerts
|

Novel oncolytic chimeric orthopoxvirus causes regression of pancreatic cancer xenografts and exhibits abscopal effect at a single low dose

Abstract: BackgroundPancreatic ductal adenocarcinoma (PDAC) has been increasing by 0.5% per year in the United States. PDAC portends a dismal prognosis and novel therapies are needed. This study describes the generation and characterization of a novel oncolytic chimeric orthopoxvirus for the treatment of pancreatic cancer.MethodsAfter chimerization and high-throughput screening, CF33 was chosen from 100 new chimeric orthopoxvirus isolates for its ability to kill pancreatic cancer cells. In vitro cytotoxicity was assayed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 41 publications
5
40
0
Order By: Relevance
“…We have previously reported the construction of a chimeric poxvirus CF33 that is more efficient in killing cancer cells than the parental poxviruses [20,21]. Sequence analysis of Fig.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We have previously reported the construction of a chimeric poxvirus CF33 that is more efficient in killing cancer cells than the parental poxviruses [20,21]. Sequence analysis of Fig.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study by Thorne et al [32] showed that among many different strains of VACVs, WR has the highest replication efficiency and cytotoxic potential in tumor cells. Interestingly, CF33 was found to have higher cytotoxic potential than all its parental viruses, including WR strain, in NCI-60 panel of cancer cell lines [20]. Very recently, Ricorde et al [33] reported the generation of a chimeric poxvirus through recombination among 4 different VACV strains: WR, Wyeth, MVA and Copenhagen.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Chen et al conducted an experiment using intraperitoneal injection of oHSV-1 to mice, suggesting that the combination of a PD-1 blockade and oHSV-1 may be an effective treatment strategy for childhood softtissue sarcoma (65). Besides, low dose of CF33 was confirmed to treat pancreatic cancer by intraperitoneal injection in vivo experiments (66). Kuryk Due to the large peritoneal area, intraperitoneal injected drugs can be absorbed faster than drugs administered the rough subcutaneous injection but slower than those delivered by intravenous injection.…”
Section: Other Routes Of Deliverymentioning
confidence: 99%